2019
DOI: 10.1111/ajt.15018
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of rescue revascularization with arterial conduits in liver transplantation

Abstract: Although aortohepatic conduits (AHCs) provide an effective technique for arterialization in liver transplantation (LT) when the native recipient artery is unusable, various publications report higher occlusion rates and impaired outcome compared to conventional anastomoses. This systematic review and meta-analysis investigates the published evidence of outcome and risk of AHCs in LT using bibliographic databases and following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
2
14
0
1
Order By: Relevance
“…Typically, when a recipient HA is unusable, the preferred arterial implantation site is the aorta with use of the donor iliac vessels as conduits if needed (18)(19)(20). Recently in a systematic review, Reese et al (21) found that this option was associated with a higher incidence of early arterial thrombosis (7% vs. 2%, P=0.001) as well as worse grafts (HR =1.38, P<0.001) and patient survival (HR =1.57, P=0.009) compared with the non-conduit groups. In their study, they reported 5-year survival at 54% and 67% for grafts and patients respectively which is similar to our findings with 5-year survival at 54.9% and 65.9% for grafts and patients respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, when a recipient HA is unusable, the preferred arterial implantation site is the aorta with use of the donor iliac vessels as conduits if needed (18)(19)(20). Recently in a systematic review, Reese et al (21) found that this option was associated with a higher incidence of early arterial thrombosis (7% vs. 2%, P=0.001) as well as worse grafts (HR =1.38, P<0.001) and patient survival (HR =1.57, P=0.009) compared with the non-conduit groups. In their study, they reported 5-year survival at 54% and 67% for grafts and patients respectively which is similar to our findings with 5-year survival at 54.9% and 65.9% for grafts and patients respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In most of these studies, the use of arterial conduits has been demonstrated to be and independent risk factor for both early and late HAT as well as for biliary complications [19,20]. Indeed, some studies have shown lower patient and graft survival rates when using arterial conduits [7,21], leading authors, such as Hibi et al [7], to recommend strictly limiting their use. Indeed, a recent meta-analysis [21] has concluded that the use of arterial conduits is a rescue option, and transplant surgeons should be alert of the potential risk of inferior outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have shown lower patient and graft survival rates when using arterial conduits [7,21], leading authors, such as Hibi et al [7], to recommend strictly limiting their use. Indeed, a recent meta-analysis [21] has concluded that the use of arterial conduits is a rescue option, and transplant surgeons should be alert of the potential risk of inferior outcome. Arterial conduits should always be reserved for salvage situations, and considering their risks, we always consider them the last alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while the technical gesture of establishing conduits adds another layer of complexity to the surgical intervention, it also has long-term consequences for the patient. Conduits present a higher risk of occlusion or thrombosis compared to the standard arterial connections and may lead to non-functioning of the graft or even the patient's death (Reese et al 2018). Hence, by choosing to deviate from the standard, the surgeon exposes the patient to a higher risk of thrombosis in order to be able to successfully perform the whole transplantation.…”
Section: Surgical Knowledge As Technical Knowledgementioning
confidence: 99%